Negative pressure wound therapy in patients with combat limb injuries: literature review - Leonid I. Bubman; Svetlana V. Topolyanskaya; Ilya M. Buriev; Igor P. Marchenko; Georgy G. Melkonyan (LLC "MEDIAFORMAT", 2024)
The review reflects modern vision about combat injuries. Particular attention is paid to injuries of the extremities and methods of their treatment. Despite advances in surgical techniques and medical technology, treating extremity combat injuries remains challenging. Regular debridement, local negative pressure wound therapy, and reconstructive surgery are currently considered the mainstay of treatment for these types of high-energy injuries. The limited literature suggests that the use of local negative pressure wound therapy in the treatment of high-energy combat wounds of the extremities reduces the incidence of wound complications, leads to a significant reduction in the size of the wound surface, cleanses wounds, stimulates the formation of granulation tissue and, ultimately, promotes wound closure. The use of the local negative pressure wound therapy has become an important method for the treatment of combat injuries, but its use in the treatment of gunshot and mine-blast wounds has not yet been sufficiently studied, which is primarily due to the difficult conditions for conducting scientific research during combat operations.